Needs Analysis of Development of Digital-Based Vertical Jump Tests - Yusfi, Herri; Solahuddin, Soleh; Syamsuramel, Syamsuramel; Giartama, Giartama; Destriani, Destriani (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
This study aims to determine the need for the development of digital-based vertical jump test equipment. This research is a survey research using a non-structural questionnaire which has been prepared to be filled in by the research subjects. Six statements were compiled in this research questionnaire to find out how much is needed for the development of digital-based vertical jump test kits.146 participants consisting of students, teachers, and physical education lecturers in South Sumatra filled out questionnaires through the google form media. The survey results showed that the majority of participants experienced difficulties during the vertical jump test and most of them thought that the vertical jump measurement instruments used were inaccurate. All participants agreed with the development of the vertical jump measurement instrument from manual to digital. The results of this study will be used as a consideration to develop a vertical jump test instrument that has a good level of validity and is relatively affordable.